Educational Cooperation Development Plan at SMAN 1 Sitiung, Dhamasraya Regency - Oktawira, Leni; Apriyenti, Apriyenti; Asmendri, Asmendri; Sari, Milya; Limei, Sun (al-fikrah: Jurnal Manajemen Pendidikan, 2024)
Cooperation in the field of education is a form of multi-level cooperation between various parties involved in the world of education, including government, educational institutions, industry, and society. The main objective of this cooperation is to improve the quality and relevance of education throughout the region. The results of this study are the development plan for cooperation between schools and related agencies in Dharmasraya including: (1) Health: Sitiung Health Center through UKS to improve student health (2) Public Services: Dharmasraya Police through the "Hallo Pak Kapolres" program to improve interaction with the community (3) Environment: Dharmasraya Regency DLH to work together to clean the environment. (4) Literacy: Dharmasraya Regional Library and schools work together to add to the collection and foster a love of reading. The development plan for cooperation between schools and Sitiung Health Center, Dharmasraya Police, and Dharmasraya Regional Library can provide great benefits in increasing awareness of health, school environmental safety, and literacy among students.